2016
DOI: 10.1098/rspa.2016.0047
|View full text |Cite
|
Sign up to set email alerts
|

An optimal tuning strategy for tidal turbines

Abstract: Tuning wind and tidal turbines is critical to maximizing their power output. Adopting a wind turbine tuning strategy of maximizing the output at any given time is shown to be an extremely poor strategy for large arrays of tidal turbines in channels. This 'impatient-tuning strategy' results in far lower power output, much higher structural loads and greater environmental impacts due to flow reduction than an existing 'patient-tuning strategy' which maximizes the power output averaged over the tidal cycle. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(33 citation statements)
references
References 27 publications
1
32
0
Order By: Relevance
“…For the first strategy, k is adjusted at each time step to ensure that C P is maximised at each instant throughout the tidal cycle. Vennell (2016) has shown this 'impatient' tuning strategy, which is widely used in the wind energy industry, to be less beneficial for tidal turbines and so, here, the impatient strategy is used simply as a baseline for comparison.…”
Section: Strategy 1: Impatient Turbine Tuningmentioning
confidence: 99%
See 3 more Smart Citations
“…For the first strategy, k is adjusted at each time step to ensure that C P is maximised at each instant throughout the tidal cycle. Vennell (2016) has shown this 'impatient' tuning strategy, which is widely used in the wind energy industry, to be less beneficial for tidal turbines and so, here, the impatient strategy is used simply as a baseline for comparison.…”
Section: Strategy 1: Impatient Turbine Tuningmentioning
confidence: 99%
“…By combining the simple tidal channel and bounded actuator disc models of Garrett andCummins (2005, 2007), Vennell (2010) showed that for turbines in channels, the maximum power depends not only on the power coefficient, but also on the thrust coefficient, which, together with the channel's natural dynamic balance, determines the throughflow velocity. Vennell (2010) also showed that large, optimally tuned turbine arrays can realise most of a channel's energy potential, and later demonstrated, following Adcock (2012), that varying the tuning over the tidal cycle can produce a higher power output, often without increasing the maximum loading on the turbines and whilst also maintaining a higher channel flow rate (Vennell 2016).…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…The wake velocity coefficients are kept constant in time because it is assumed that the additional amount of power that may be gained by varying the turbine resistance over daily (Vennell and Adcock 2014;Vennell 2016) or spring-neap cycles ) is relatively small. Local blockage ratios of 0.1 and 0.4 are chosen to represent moderately sized and very large developments, respectively, and different combinations of rows are considered.…”
Section: Resource Assessmentmentioning
confidence: 99%